Species generalization and differences in Hedgehog pathway regulation of fungiform and circumvallate papilla taste function and somatosensation demonstrated with sonidegib. Issue 1 (December 2018) - Kumari, A.; Yokota, Y.; Li, L.; Bradley, R.; Mistretta, C.
Abstract Species generalization in the profound, modality-specific effects of Hedgehog pathway inhibition (HPI) in taste organ homeostasis and sensation is shown. With the HPI, cancer drug sonidegib, we demonstrate that the rat taste system, in addition to mouse, is regulated by Hedgehog signaling. After sonidegib treatment for 16–36 days in rat, there is loss of taste buds (TB) in soft palate, in fungiform (FP) and circumvallate papillae (CV), and elimination of taste responses from chorda tympani and glossopharyngeal nerves. The retained innervation in FP and CV during HPI cannot sustain TB. Responses to tactile stimuli are not altered, and temperature responses are reduced only after 28 days treatment, demonstrating modality-specific effects. Rat FP and neural effects are similar to those in mouse whereas TB and neural response effects from the rat CV are much more severe. When recovery is introduced in mouse after prolonged, 48 days HPI, the TB in CV are restored whereas those in FP are not. Overall, Hedgehog signaling regulation is shown to generalize to the rat taste system, and the modality-specific controls in taste organ sensation are affirmed. The reported, debilitating taste disturbances in patients who use HPI drugs can be better understood based on these data.